The application of the Common Design Recommendations (CDR) in assessing restorative green outdoor environments - Adnan, Siti Nur Fathirah; Abdul Shukor, Shureen Faris (Faculty of Design & Architecture, Universiti Putra Malaysia, 2015)
The main purpose of this paper is to analyse green outdoor environment (GOE) at a hospital in Malaysia with the aim of identifying the restorative design characteristics found at the gardens. Serdang Hospital was selected due to the existing of gardens using the therapeutic concept. The gardens were also selected due to their accessibility to all users who are mainly the patients, visitors and staffs. A survey tool called the Common Design Recommendation (CDR) which consists of seven themes (location and view; accessibility; layout and space; seating arrangements; planting; design details; and practical services) were used to test the restorative quality of the gardens. The results have shown that two of the CDR themes (location and view; and accessibility) have the highest score among the 19 gardens found at the hospital. The paper also discusses suggestions on how to improve the hospital gardens in Malaysian hospitals.